Mapping Eco-Labelling Research Trends with a Bibliometric Perspective - Judijanto, Loso (West Science Business and Management, 2025)
Eco-labelling has emerged as a vital tool in promoting sustainable consumption and production by informing consumers about the environmental impacts of products and services. Over the past two decades, the body of research on eco-labelling has expanded significantly across multiple disciplines, yet remains fragmented in terms of thematic focus and geographic collaboration. This study aims to systematically map the development of eco-labelling research using bibliometric analysis, with data sourced from the Scopus database covering the period 2000–2024. Using VOSviewer software, co-citation, co-authorship, keyword co-occurrence, overlay, and density visualizations were employed to analyze the intellectual structure, collaboration patterns, and evolving research themes. The findings reveal three major thematic clusters: consumer behavior and willingness to pay, sustainability and environmental performance, and institutional certification systems. Key contributors such as Teisl, Thøgersen, and Cashore were identified, along with leading countries including the United States, Italy, and France. The temporal analysis shows a thematic shift toward sustainable development, innovation, and climate change in recent years. This study offers a comprehensive overview of eco-labelling literature, highlights gaps in producer-side research and technological integration, and provides guidance for future scholarship and policy innovation in sustainable labeling practices.
Keywords: Eco-labelling; Bibliometric analysis; Sustainable development; Consumer behavior